A rapid method for quantifying cytoplasmic versus nuclear localization in endogenous peripheral blood leukocytes by conventional flow cytometry. Issue 4 (30th March 2017) - Brittain, George C.; Gulnik, Sergei
Abstract: A biochemical system and method have been developed to enable the quantitative measurement of cytoplasmic versus nuclear localization within cells in whole blood. Compared with the analyses of nuclear localization by western blot or fluorescence microscopy, this system saves a lot of time and resources by eliminating the necessity of purification and culturing steps, and generates data that are free from the errors and artifacts associated with using tumor cell lines or calculating nuclear signals from 2D images. This user‐friendly system enables the analysis of cell signaling within peripheral blood cells in their endogenous environment, including measuring the kinetics of nuclear translocation for transcription factors without requiring protein modifications. We first demonstrated the efficiency and specificity of this system for targeting nuclear epitopes, and verified the results by fluorescence microscopy. Next, the power of the technique to analyze LPS‐induced signaling in peripheral blood monocytes was demonstrated. Finally, both FoxP3 localization and IL‐2‐induced STAT5 signaling in regulatory T cells were analyzed. We conclude that this system can be a useful tool for enabling multidimensional molecular‐biological analyses of cell signaling within endogenous peripheral blood cells by conventional flow cytometry. © 2017 International Society for Advancement of Cytometry